Characterisation of polymers for anti-counterfeit labels - Tan, Li Jie (2018)
This project aims to amalgamate shape memory effect in polymers with Anti-counterfeit Labels (ACLs) to create anti-heat transfer ACLs that shows evidence of heating. The evidence warns the consumers and manufacturers if their product had tampered. Thereby, preventing the abuse of authentic labels in counterfeited products. This project attempted to characterise and augment commercialised polymers to produce low-cost anti-heat transfer ACLs. The polymers were programmed by impression or indentation to achieve multiple pre-strain fields, or by incision to have designed cracks. The programming was done to enable polymers to produce desired shape memory effect when heated. Shape memory effect of these polymers, temperatures which the shape memory effect occurred, and other selected material characteristics were collected, analysed and discussed to develop low-cost anti-heat transfer ACLs.